Prospective clinical evaluation of the accuracy of 16S rRNA real-time PCR assay for the diagnosis of melioidosis - Narisara Chantratita (2018)
The accuracy of a Burkholderia pseudomallei 16s rRNA real-time PCR assay was evaluated against culture for the diagnosis of melioidosis in Thailand. A total of 846 samples were obtained from 383 patients with suspected melioidosis. One or more specimens were PCR positive for 47 of 77 patients with culture-proven melioidosis (sensitivity 61.0%, 95% CI: 49.2-72.0%). PCR was negative for all 306 patients who were culture negative for B. pseudomallei (specificity 100%, 95% CI: 98.8-100%). Diagnostic sensitivity of PCR was 22.7% for patients who were culture positive for blood only, compared with 79.4% for patients who were culture positive for samples other than blood. The median (interquartile range) B. pseudomallei colony count in blood for 44 of 77 patients with positive blood cultures was 2.4 CFU/ml (0.2-13.5 CFU/ml); this may explain the low sensitivity of PCR for this specimen. The PCR assay described here is not sufficiently sensitive to replace culture in our clinical setting. Copyright © 2007 by The American Society of Tropical Medicine and Hygiene.